Bureaucratic Reform Strategy In Improving The Quality Of Public Services By Implementing Bureaucratic Communication Model in Cimahi City - Titin Rohayatin; Agus Subagyo; Agustina Setiawan; Siti Munawaroh; Widuri Wulandari (Universitas Medan Area, 2022)
This study aims to look at the bureaucratic reform strategy for improving public services in Cimahi City. This study uses a qualitative descriptive method, namely interview data collection techniques, literature study, and observation. Research result; mapping of the condition of the Cimahi City Regional Government in terms of institutions, management, bureaucratic ethics, a description of the reasons why bureaucratic reform is needed, and the formulation of general guidelines for bureaucratic reform strategies that refer to the Grand Design of bureaucratic reform through 8 (eight) areas of change, namely: Mental Apparatus, Legislation -Invitation, Performance Accountability, Management, Supervision, Institutional, Apparatus HR, and Public Services. And the formation of a model of government bureaucratic communication. The bureaucratic communication model is expected to be able to accelerate the process of bureaucratic reform in government. The models are SR (Stimulus-Response) model, Aristotels Linear communication model, Linear development communication model (Shannon and Wever), SMCR Communication Model (Sender, Message, Channel, and Receiver), Bureaucratic Communication Process model, and Bureaucratic communication model. With the government bureaucratic communication model in public services, it is expected to create quality and effective communication.